Fluorinated lipid nanoparticles enable real-time tracking of mRNA delivery and uncover spatiotemporal mechanisms of immune activation - Kairu Xie; Lijun Zhu; Mojie Duan; Yu Fu; Haiqiang Wang; Yuhan Shen; Yu Li; Ruifang Wang; Zhong-Xing Jiang; Shizhen Chen; Jung Soo Suk; Daiqin Chen; et al. (Proceedings of the National Academy of Sciences, 2026)
Messenger RNA (mRNA) vaccines rely on lipid nanoparticles (LNPs) for in vivo delivery, yet conventional formulations exhibit inefficient tissue targeting, undesired hepatic accumulation, and limited understanding of the delivery–response relationship, constraining their therapeutic precision and safety. Here, we report the development of fluorinated LNPs (FLNPs) that enable real-time tracking of mRNA biodistribution and expression via 19 F magnetic resonance spectroscopy/imaging (NMR/MRI)” rather than “magnetic resonance spectroscopy/MRI (NMR). These FLNPs retain robust protein expression comparable to clinical LNPs, while reducing liver accumulation by 94.6%. By integrating fluorine signal quantification with spatial analysis of mRNA translation and antigen presentation, we establish a direct correlation between carrier localization, antigen expression kinetics, and immune cell trafficking. Specifically, we show that antigen-presenting cells internalize FLNP-mRNA at the injection site and subsequently migrate to draining lymph nodes, enabling localized immune priming with minimal systemic exposure. This work provides mechanistic evidence linking in vivo nanocarrier trafficking with spatiotemporal immune activation, offering insights into how delivery kinetics govern vaccine efficacy. The FLNP platform thus enables both precision mRNA delivery and noninvasive tracking, representing a powerful tool for mechanistic studies and rational design of next-generation mRNA vaccines.